La planificación estratégica en el desarrollo profesional de los docentes de la unidad educativa “10 de enero”, del cantón San Miguel, provincia Bolívar, durante el período2014-2015 - Morales Lucio, Eva Concepción (2015)
In the course of time, mankind has gestated great men and women who have left an everlasting mark of values and principles, with a vision of the future and what needs to be done to achieve big dreams and ideals of man. The most important qualities of the leader of yesterday have been and are to this day to inspire and watch. This premise leads us to the plane of the same training be initiated at home, is strengthened in the classroom where they share common interests, standards of conduct and interaction develop. This thesis wishes to contribute to institutional development through strategic planning in the Education Unit "January 10th." This research is primarily aimed at those institutions that have competitive weaknesses in strategic planning, institutional development, decision decisions, motivation and coordination. This plan divided into working sections through the implementation of workshops called "actions" that include objectives, strategic activities, resources and duration so as to achieve the intent of it. In Chapter I, a thorough review of the issues is made according to the operationalization of the variables in order to support the hypothesis, argumentation and verification with the theories raised on the subject under investigation. In Chapter II, the methodology proposed in this work, as data collection instruments use primary and secondary (Polls) sources is presented. The population under research consisted of 225 people; of which 21 are teachers working in the school, and 204 students in basic general education, I went to an important methodological field and properly selected, more logical historical methods, deductive, inductive, purposeful dialectic method of 12 investigation action They contributed in the search for truth, developing each change strategies to improve strategic planning in the scene. In Chapter III, analysis, discussion of the results obtained during the implementation of the survey is exposed due to perform tabulations of research work, such as strategic planning, professional development, the hypothesis is also tested by descriptive statistics and qualitative analysis, leading to the conclusions, recommendations, bibliographic finally Annexes and scientific article.